Ritual and Self-Cultivation in the Daoist Practice of “Oblatory Refinement” - Capitanio, Joshua (Numen, 2019)
This article describes a Daoist salvific ritual called jilian 祭鍊, “oblatory refinement,” as presented within a ritual manual written by Zheng Sixiao 鄭思肖 (1241-1318). Zheng’s formulation of this ritual and his extensive commentary on its individual elements show that he regards this ritual not only as a means of achieving salvation for others, but also as a complete system of self-cultivation that is capable of enabling the practitioner’s self-apotheosis. After discussing the historical background of the ritual and describing its various stages, I analyze Zheng’s approach to ritual practice and his understanding of the relationship between ritual and self-cultivation, both of which are characterized by his emphasis on the quality of “sincerity” (cheng 誠). Ultimately, I argue that the Daoist notion of an “inner,” cognitive and affective dimension of ritual practice points to useful ways of supplementing contemporary theoretical understandings of ritual that focus primarily, if not exclusively, on the formal aspects and social contexts of ritual activities.